Design And Manufacture Of Tools Automatic Feeding And Drinking In Farm Chickens Arduino Microcontroller-Based - Alexius Ulan Bani; Fifto Nugroho; Aditya Teguh Arsyendo (Journal of Mathematics and Technology (MATECH), 2022)
Feeding automatic chickens aims to build an automatic feeding and drinking device for chickens to facilitate the work of chicken farmers. Conducting observations accurately, the literature study method collects data related to the topic. Hardware design process and how the tool works. Software is a systematic process program that functions as a tool command, tool testing by implementing tool work. The result of the research is that the tool can work well as desired and the power is stable for each component used.